Reduction and Expansion in Microsporidian Genome Evolution: New Insights from Comparative Genomics - Nakjang, Sirintra (Oxford University Press, 2013)
Microsporidia are an abundant group of obligate intracellular parasites of other eukaryotes, including immunocompromised humans, but the molecular basis of their intracellular lifestyle and pathobiology are poorly understood. New genomes from a taxonomically broad range of microsporidians, complemented by published expression data, provide an opportunity for comparative analyses to identify conserved and lineage-specific patterns of microsporidian genome evolution that have underpinned this success. In this study, we infer that a dramatic bottleneck in the last common microsporidian ancestor (LCMA) left a small conserved core of genes that was subsequently embellished by gene family expansion driven by gene acquisition in different lineages. Novel expressed protein families represent a substantial fraction of sequenced microsporidian genomes and are significantly enriched for signals consistent with secretion or membrane location. Further evidence of selection is inferred from the gain and reciprocal loss of functional domains between paralogous genes, for example, affecting transport proteins. Gene expansions among transporter families preferentially affect those that are located on the plasma membrane of model organisms, consistent with recruitment to plug conserved gaps in microsporidian biosynthesis and metabolism. Core microsporidian genes shared with other eukaryotes are enriched in orthologs that, in yeast, are highly expressed, highly connected, and often essential, consistent with strong negative selection against further reduction of the conserved gene set since the LCMA. Our study reveals that microsporidian genome evolution is a highly dynamic process that has balanced constraint, reductive evolution, and genome expansion during adaptation to an extraordinarily successful obligate intracellular lifestyle.